Gamification in museums: systematic review of scientific literature on educational initiatives based on video games and their impact on cultural learning (2004-2024) - González-Liendo, Julio (2026)
In recent decades, gamification has emerged as an innovative strategy to enhance museum educational engagement. This study presents a systematic literature review analyzing research published between 2004 and 2024 in the Scopus and Web of Science databases, aimed at examining how gamification has been addressed in museum contexts and what its main characteristics, methodological approaches, and reported effects on cultural learning are. The focus is on museum-based educational initiatives supported by gamification tools. Findings show that game-inspired principles foster motivation, engagement, and learning among visitors, strengthening their relationship with cultural heritage. The review also identifies emerging trends in the design of gamified strategies that integrate dynamics, mechanics, and game components, adapted to both technological and non-technological contexts. At the same time, it highlights persistent barriers, such as perceptions of technological dependence and the limited adoption in smaller museums. We conclude that, while gamification positively impacts the museum learning experience, further interdisciplinary collaboration and the development of sustainable, evidence-based practices are needed to maximize its potential.